2005
DOI: 10.1111/j.1745-4603.2005.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Rennet‐induced Gels During the Coagulation and Cutting Process: Impact of Processing Conditions

Abstract: The effects of gelation temperature (GT), pH, milk solids nonfat (MSNF) content and aging time on the small and large deformation rheological properties of rennet‐induced skim milk gels were studied. Small amplitude oscillatory rheometry (SAOR) was used to study gel formation. A constant shear rate was applied to gels of various ages to try to simulate the cutting process used in cheese vats. Second‐order polynomial models successfully predicted (R2 ≥ 0.83) the relationship between processing parameters and rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 24 publications
10
37
0
Order By: Relevance
“…3c, d). These results were in agreement with those of Ramasubramanian et al (2014) who observed an increase of G 0 for calcium-induced cow milk gels with increase of frequency from 0.1 to 10 Hz, reflecting that the formed bonds in the gels matrix have less time to relax when the time scale of the applied stress is shorter (Mishra et al 2005). Similar results for control milk gels were obtained with added phosphate (Fig.…”
Section: Size Distribution Of Casein Micellessupporting
confidence: 82%
“…3c, d). These results were in agreement with those of Ramasubramanian et al (2014) who observed an increase of G 0 for calcium-induced cow milk gels with increase of frequency from 0.1 to 10 Hz, reflecting that the formed bonds in the gels matrix have less time to relax when the time scale of the applied stress is shorter (Mishra et al 2005). Similar results for control milk gels were obtained with added phosphate (Fig.…”
Section: Size Distribution Of Casein Micellessupporting
confidence: 82%
“…The influence of milk pH at renneting (often referred to in other studies as the gelation or coagulation pH) on the properties of rennetinduced gel has been reported by various groups (Daviau, Famelart, Pierre, Goudedranche, & Maubois, 2000;Esteves, Lucey, Wang, & Pires, 2003;Hannon et al, 2006;Lucey, Johnson, & Horne, 2003;Mishra et al, 2005;Zoon et al, 1989). These reports offer valuable insights but are often limited to gels made using skim milk (Daviau et al, 2000;Esteves et al, 2003), non-fat milk (Mishra et al, 2005), ultrafiltered milk (Hannon et al, 2006) or reconstituted skim milk powder (Mishra et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…These reports offer valuable insights but are often limited to gels made using skim milk (Daviau et al, 2000;Esteves et al, 2003), non-fat milk (Mishra et al, 2005), ultrafiltered milk (Hannon et al, 2006) or reconstituted skim milk powder (Mishra et al, 2005). Furthermore, the microstructure of the gel, curd or cheese and the composition of the final cheese product has not been the focus in the majority of these studies.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations